The relationship between whiplash and temporomandibular joint dysfunction - Brady, Charles L. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Anatomy, 2007)
"Whiplash" describes the mechanism of retroflexion followed by flexion of the neck that occurs when the occupant of a motor vehicle is impacted from behind by another vehicle with the occupant of the impacted vehicle being unaware of the impending impact. This thesis describes work carried out to investigate the possibility that injury can occur to the jaw joint (i.e. the temporomandibular joint) during a "whiplash" event. A review of the literature showed that there is a body of clinical evidence pointing to an aetiological relationship between "whiplash” and injuries to the TMJ. However much as in an earlier debate regarding injury to the cervical region, these claims have led to dispute regarding the viability of such injuries occurring particularly as the jaw is not subjected to direct trauma in the classical "whiplash" event.
Keywords: Anatomy, Ph.D.; Ph.D. Trinity College Dublin